A comparison study of the effect of clinical experience and workplace on the availability and use of biophysical agents by Icelandic physical therapists - Hulda Hlíðkvist Þorgeirsdóttir 1995- (2024)
Background: The use of biophysical agents (BPAs) in physical therapy varies globally. While significant research has been conducted internationally, the availability and specific usage patterns among Icelandic physical therapists remain unexplored formally until this study. Objective: The thesis aims to analyze the disparities in the BPAs utilization between novice and experienced physical therapists in Iceland, and compare these patterns with similar studies done in other countries. Also, to compare how workplace environments, private practice vs. non-private practice, affect the BPA usage. Methods: A cross-sectional survey was distributed among Icelandic physical therapists, categorizing the BPAs availability and usage. A total of 223 participants initially took part in the survey, a 34% response rate. Responses from therapists with five or less years of experience were compared to experienced therapists (more than 20 years experience) and responses from private practice therapists were compared to non-private practice therapists. Statistical analysis, including the Mann-Whitney U test, was employed to identify any significant differences in usage patterns between novice and experienced physical therapists, as well as across different workplace environments. Results: The results indicated that experienced physical therapists use biophysical agents more frequently than their novice colleagues, particularly when it comes to paraffin wax, ultrasound, and biofeedback. The most used biophysical agents by both novice and experienced therapists were low-level laser therapy (LLLT), hot packs, and transcutaneous electrical nerve stimulation (TENS). Workplace environment significantly influences BPAs choices. Physical therapists in private practice were more likely to use LLLT, mechanical traction, and extracorporeal shockwave therapy (ESWT). In contrast, therapists in non-private practice used hot packs, paraffin wax, and whirlpool significantly more than their colleagues in private practice. The most used biophysical ...